2019
DOI: 10.1101/650465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Down regulation ofHmgcrin response to Influenza A infection is independent of the IFN response in human cells

Abstract: Previous studies have demonstrated that the product of the Interferon stimulated gene Ch25h, 25-Hydroxycholestrol, provides an immediate and rapid mechanism for down-regulating sterol biosynthesis, through the inhibition of Hmgcr gene expression and proteolytic degradation of HMGCR protein. Further studies provide evidence that inhibition of the sterol biosynthesis pathway by 25-HC has broad antiviral effects. In this study, Influenza A virus (IAV) replication was inhibited in cells treated with Fluvastatin or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, cholesterol is known to modulate IAV trafficking, and depletion of cholesterol disrupts IAV transport after cellular entry ( 60 , 62 , 64 , 76 ). Mehrbod et al ( 62 ) showed that simvastatin prevents RhoA prenylation, which is key to arrangement of the actin cytoskeleton for endosome trafficking, and results in inefficient transport of viral genomes into the nucleus for replication ( Figure 1 ).…”
Section: Iav Internalization Relies On Lipid Raftsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cholesterol is known to modulate IAV trafficking, and depletion of cholesterol disrupts IAV transport after cellular entry ( 60 , 62 , 64 , 76 ). Mehrbod et al ( 62 ) showed that simvastatin prevents RhoA prenylation, which is key to arrangement of the actin cytoskeleton for endosome trafficking, and results in inefficient transport of viral genomes into the nucleus for replication ( Figure 1 ).…”
Section: Iav Internalization Relies On Lipid Raftsmentioning
confidence: 99%
“…In addition, cholesterol is known to modulate IAV trafficking, and depletion of cholesterol disrupts IAV transport after cellular entry (60, 62,64,76). Mehrbod et al (62) showed that simvastatin prevents RhoA prenylation, which is key to Effect of statins on the IAV life cycle and the host immune response.…”
Section: Iav Internalization Relies On Lipid Raftsmentioning
confidence: 99%